AB0534 Podocytic Abnormalities in SLE – Parallel Mechanism Affecting Kidney. (9th June 2015) - Vankalakunti, M.; Rao, V.K.R.; Dharmanand, B.; Bhat, R.; Guptha, V.; Rani, S.; Umesh, L.; Nalloor, S.; Kiran, J.; Bipin, M.; Rampure, S.; Babu, K.; et al.
Abstract : Background: Renal involvement occurs in 40-70% of SLE patients. Biopsy is performed to look for the class of lupus nephritis. Objectives: We describe clinicopathological and treatment outcomes of ten cases of SLE podocytic lesions. Methods: A retrospective evaluation of 10, 482 native renal biopsies referred to our institute during the period Jan 2010-Dec 2014 revealed 710 (6.8%) cases of lupus nephritis (LN). Distinct ten cases with biopsy proven LN with podocytic lesions formed the current case-series. Detailed clinical, lab investigations, renal biopsy, treatment & follow-up information were obtained from medical records. Results: All were females aged between 16-46 yrs and duration of illness was 1 week–8 years. Clinical findings included nephrotic syndrome with hypoalbuminemia in all (2 weeks-5 months duration), renal insufficiency in four and extra-renal flare of lupus in one. Urinalysis revealed ≥2+ proteinuria in all. Urine sediments were bland sediments in 6 cases & active sediments in 2 cases. Proteinuria ranged between 3–24 gm/day. Renal histology showed isolated podocytopathies in seven cases [Focal Segmental Glomerulosclerosis (FSGS), tip variant (1); Minimal Change Nephrotic Syndrome (MCNS) with class-II LN (5); isolated collapsing FSGS (1)] and combination of proliferative lupus nephritis and podocytopathies in three cases [collapsing FSGS with class-III LN (1); collapsing FSGS with class-IV LN (1); & collapsing FSGS with class-VI LN (1)]. EM study was available in 2 cases which revealed diffuse effacement of foot processes. Isolated podocytopathy was treated with steroids (1 mg/kg) and hydroxychloroquine. Complete clinical remission was achieved in 4/7 cases with isolated podocytopathy during 3-7 months period. Among the three cases with podocytopathy and renal insufficiency, one progressed to end stage kidney disease, two required cyclophosphamide and steroids. Conclusions: Podocytic lesions in lupus, although generally present as nephrotic range proteinuria, it could also accentuate the damage caused by immune-mediated glomerular injury. In our cases, isolated podocytic lesions responded well to steroids and hydroxychloroquine, but those with associated renal dysfunction required aggressive treatment. Although biopsy is required to look for the class, our cases highlight the importance of recognizing podocytopathy as an alternative cause for nephrotic syndrome in lupus and raises the discussion of adding a sub-class to the ISN/ RPS system for guiding therapy and prognosis. Disclosure of Interest: None declared